Analisis Faktor-Faktor Yang Mempengaruhi Indeks Prestasi Kumulatif (IPK) Mahasiswa/i Jurusan Ekonomi Pembangunan FEB Universitas Palangka Raya - Ira Veronika Girsang; Kristi Damayanti.G; Junita Perangin-angin; Yuliana Yuliana; Diana Rezi Lumbantoruan; Rahman Rahman; Alfin Rabil Awalam; Hairun Nisa; Dicky Perwira Ompusunggu (Nian Tana Sikka : Jurnal ilmiah Mahasiswa, 2024)
The purpose of this study is to see the factors that have the most influence on student GPA such as learning at home, the quality of teaching on campus, and the organisations they join. This study uses a type of quantitative research with a descriptive approach, with multiple regression analysis. The classical assumption test passed the test. Result: The variable number of organisations followed, the amount of campus teaching, and the amount of study at home together contributed 69.2% to the student's cumulative grade point average, the remaining 30.8% was influenced by other factors outside the model. The three independent variables simultaneously have a significant effect on the cumulative grade point average based on the F test. In the t test, the variables of learning at home and teaching on campus play a positive and significant role in improving student academic achievement as measured by GPA, while the number of organisations followed has no significant effect with a negative relationship.